Complementary and dose‐dependent action of AtCCS52A isoforms in endoreduplication and plant size control. Issue 4 (25th March 2013) - Baloban, Mikhail; Vanstraelen, Marleen; Tarayre, Sylvie; Reuzeau, Christophe; Cultrone, Antonietta; Mergaert, Peter; Kondorosi, Eva
Summary The dimension of organs depends on the number and the size of their component cells. Formation of polyploid cells by endoreduplication cycles is predominantly associated with increases in the cell size and implicated in organ growth. In plants, the CCS52A proteins play a major role in the switch from mitotic to endoreduplication cycles controlling thus the number of mitotic cells and the endoreduplication events in the differentiating cells. Arabidopsis has two CCS52A isoforms; AtCCS52A1 and AtCCS52A2. Here we focused on their roles in endoreduplication and cell size control during plant development. We demonstrate their complementary and dose‐dependent actions that are dependent on their expression patterns. Moreover, the impact of CCS52A overexpression on organ size in transgenic plants was dependent on the expression level; while enhanced expression of the CCS52A genes positively correlated with the ploidy levels, organ sizes were negatively affected by strong overexpression whereas milder overexpression resulted in a significant increase in the organ sizes. Taken together, these finding support both complementary and dose‐dependent actions for the Arabidopsis CCS52A isoforms in plant development and demonstrate that elevated ectopic CCS52A expression positively correlates with organ size, opening a route to higher biomass production.